Turning the tide - Staddon, Patsy (Groupwork, 2014)
This paper’s title reflects the wishes of very many women to turn the tide of alcohol treatment back from models of groupwork which they find disabling and a cause of harm to self-esteem, rather than one which acts as a tool for empowerment. The paper itself explains how a very simple style of groupwork, designed and run by women alcohol service users, outside the realms of treatment centres, can be effective as a tool for empowerment.